PENGARUH MOTIVASI KERJA DAN KONFLIK KERJA TERHADAP KINERJA GURU DI SEKOLAH DASAR NEGERI 001 KECAMATAN UKUI - Fikria Sari; Zaka Hadikusuma Ramadan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to analyze the influence of work motivation and work conflict on teacher performance at State Elementary School 001, Ukui District. This research uses the variables Work Motivation and Work Conflict as independent variables and Teacher Performance as the dependent variable with a descriptive quantitative research method and a sample of 39 people and using a saturated sampling method. The data analysis method used in this research is multiple linear regression technique. The results of this analysis show that work motivation and work conflict influence teacher performance at State Elementary School 001, Ukui District. From the hypothesis test obtained, the research hypothesis Hypothesis 1, Hypothesis 2 and Hypothesis 3 are accepted.